2020
DOI: 10.1109/access.2020.3000780
|View full text |Cite
|
Sign up to set email alerts
|

Using User Behavior to Measure Privacy on Online Social Networks

Abstract: Because social networks exemplify the phenomenon of homogeneity in complex networks, researchers generally believe that a user's privacy disclosure is closely related to that of the users around them, but we find that the related users studied in previous methods were not correct. That is, the analyzed user groups may have had nothing to do with the privacy disclosure of the target users. Since private information is time-sensitive, information held by users who are no longer in the same environment as the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We summarize and compare the famous AI-based G anonymization techniques used for PPGP in Table 6. [175] Technical Predicts the SI in a G using ML and suggests how to safeguard it NB, SVM, RF S Yin et al [176] Technical Strikes a balance between privacy and utility in distributing G k-means algorithm R Wang et al [177] Technical Privacy preservation of degree information in releasing G k-means algorithm R Ju et al [178] Technical Strong privacy of V in G along with higher accuracy and utility k-means algorithm R Zheng et al [179] Technical Strong privacy of V in G and fewer changes to G's structure GNN algorithm R Paul et al [180] Technical Preserves the structural properties of G in anonymization process k-means algorithm R Hoang et al [181] Technical Preserves the privacy of SN users modelled via knowledge of G k-ad algorithm R Hoang et al [182] Technical Preserves the privacy of SN users when G is subject to multiple releases CTKGA algorithm R Chen et al [183] Technical Privacy preservation of SN users when G contains outliers and categorical attributes DBSCAN clustering R Narula et al [184] Technical Privacy preservation of identity and emotion-related information in OSN data CNN algorithm R Zitouni et al [185] Technical Privacy preservation by concealing the identity in image data CNN and LSTM R Ahmed et al [186] Technical Privacy preservation by concealing the identity and other SI in images Neural Network R Matheswaran et al [187] Technical Privacy preservation of image data in retrieval and storage in clouds Watermarking R Li et al [188] Technical Both anonymity-and utility-preserving solutions for OSN data GAN Algorithm R Lu et al [189] Technical Privacy preservation by reducing the prediction accuracy of sensitive links in G VGAE and ARVGA R Li et al [190] Technical Privacy preservation using profile, graph structure, and behavioral information GCNN algorithm R Wanda et al [191] Technical Privacy preservation of vulnerable nodes in G using dynamic deep learning CNN architecture R Li et al [192] Technical Privacy preservation of users when a user's job/education-place changes with time Supervised ML R Bioglio et al [193] Technical Privacy preservation of contents in OSN platforms based on sensitivity analysis Deep NN R Hermansson et al [194] Technical Preserves better accuracy for data-mining and analytical tasks from G SVM algorithm R Kalunge et al [195] Technical Preserves better utility (path length and IL) ...…”
Section: Artificial Intelligence-based Graph Anonymization Methodsmentioning
confidence: 99%
“…We summarize and compare the famous AI-based G anonymization techniques used for PPGP in Table 6. [175] Technical Predicts the SI in a G using ML and suggests how to safeguard it NB, SVM, RF S Yin et al [176] Technical Strikes a balance between privacy and utility in distributing G k-means algorithm R Wang et al [177] Technical Privacy preservation of degree information in releasing G k-means algorithm R Ju et al [178] Technical Strong privacy of V in G along with higher accuracy and utility k-means algorithm R Zheng et al [179] Technical Strong privacy of V in G and fewer changes to G's structure GNN algorithm R Paul et al [180] Technical Preserves the structural properties of G in anonymization process k-means algorithm R Hoang et al [181] Technical Preserves the privacy of SN users modelled via knowledge of G k-ad algorithm R Hoang et al [182] Technical Preserves the privacy of SN users when G is subject to multiple releases CTKGA algorithm R Chen et al [183] Technical Privacy preservation of SN users when G contains outliers and categorical attributes DBSCAN clustering R Narula et al [184] Technical Privacy preservation of identity and emotion-related information in OSN data CNN algorithm R Zitouni et al [185] Technical Privacy preservation by concealing the identity in image data CNN and LSTM R Ahmed et al [186] Technical Privacy preservation by concealing the identity and other SI in images Neural Network R Matheswaran et al [187] Technical Privacy preservation of image data in retrieval and storage in clouds Watermarking R Li et al [188] Technical Both anonymity-and utility-preserving solutions for OSN data GAN Algorithm R Lu et al [189] Technical Privacy preservation by reducing the prediction accuracy of sensitive links in G VGAE and ARVGA R Li et al [190] Technical Privacy preservation using profile, graph structure, and behavioral information GCNN algorithm R Wanda et al [191] Technical Privacy preservation of vulnerable nodes in G using dynamic deep learning CNN architecture R Li et al [192] Technical Privacy preservation of users when a user's job/education-place changes with time Supervised ML R Bioglio et al [193] Technical Privacy preservation of contents in OSN platforms based on sensitivity analysis Deep NN R Hermansson et al [194] Technical Preserves better accuracy for data-mining and analytical tasks from G SVM algorithm R Kalunge et al [195] Technical Preserves better utility (path length and IL) ...…”
Section: Artificial Intelligence-based Graph Anonymization Methodsmentioning
confidence: 99%
“…Li et al [24] have provided a de-anonymization strategy for the heterogeneous social network in a different piece of work-the model claims to improve the detection system by using user profile and network structure information. Li et al also presents a similar work form [25]. The investigation model assesses privacy factors associated with the behavioral attributes in social networks based on structural similarity.…”
Section: B Privacy Preservation-based Approachesmentioning
confidence: 99%
“…Also, it helps the exposed users to customize their privacy level semiautomatically by limiting the number of manual operations. Li et al [231] suggested that private information in the SNs sites is time-sensitive, which means that information held by the users who are no longer in the same environment/place as the target user may no longer be reliable/true and have lost its value. The authors combined behavioral characteristics and structural similarity to accurately filter the user groups who hold the current private information of a target user for measuring a user's privacy status.…”
Section: Anomaly Detection In Online Social Network With High Detectmentioning
confidence: 99%